Perbandingan Kepuasan Konsumen Terhadap 3 Minuman Kekinian di Medan (KOI,CHATIME,KOPKEN) - David David; Hartono Hartono; Caroline Caroline; Fernando Fernando; Helen Winata (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2024)
Urban lifestyles have integrated modern drinks, and this phenomenon has had an impact on cities such as Medan in North Sumatra. The aim of this research is to compare the level of customer satisfaction with three types of contemporary drinks that are popular in Medan. This research uses quantitative research methods and uses samples randomly selected from customers who visit contemporary drink shops in various areas of Medan. The survey method is used as the main method. This research methodology is designed to collect quantitative data about consumer preferences, variables that influence satisfaction, and their perceptions of product quality, service, and price. Data analysis was carried out using appropriate statistical tools to compare the level of consumer satisfaction between the three types of modern drinks selected.